Indoor tracking with iBeacon localisation - Butt, Racheal Jia En (Nanyang Technological University, 2022)
Fitness trackers, smart home devices and energy saving buildings. These are just some of the applications coming from the Internet of Things (IoT). IoT has such a broad application spectrum that redefines how we interact with one another and the environment in an increasingly smart world. As an undergraduate student in Engineering, it is not uncommon to see students with iPads, Apple pencils, wireless earbuds and a smartphone. What all these devices have in common is the usage of Bluetooth Low Energy (BLE). In this project, we discuss how BLE is used in the application of location tracking, specifically indoor tracking in a building, and its challenges. We then build a phone app to display the findings.